Monitoring α‐synuclein multimerization in vivo. Issue 2 (25th September 2018) - Prasad, Vibha; Wasser, Yasmine; Hans, Friederike; Goswami, Anand; Katona, Istvan; Outeiro, Tiago F.; Kahle, Philipp J.; Schulz, Jörg B.; Voigt, Aaron
ABSTRACT: The pathophysiology of Parkinson's disease is characterized by the abnormal accumulation of α‐synuclein (α‐Syn), eventually resulting in the formation of Lewy bodies and neurites in surviving neurons in the brain. Although α‐Syn aggregation has been extensively studied in vitro, there is limited in vivo knowledge on α‐Syn aggregation. Here, we used the powerful genetics of Drosophila melanogaster and developed an in vivo assay to monitor α‐Syn accumulation by using a bimolecular fluorescence complementation assay. We found that both genetic and pharmacologic manipulations affected α‐Syn accumulation. Interestingly, we also found that alterations in the cellular protein degradation mechanisms strongly influenced α‐Syn accumulation. Administration of compounds identified as risk factors for Parkinson's disease, such as rotenone or heavy metal ions, had only mild or even no impact on α‐Syn accumulation in vivo . Finally, we show that increasing phosphorylation of α‐Syn at serine 129 enhances the accumulation and toxicity of α‐Syn. Altogether, our study establishes a novel model to study α‐Syn accumulation and illustrates the complexity of manipulating proteostasis in vivo .—Prasad, V., Wasser, Y., Hans, F., Goswami, A., Katona, I., Outeiro, T. F., Kahle, P. J., Schulz, J. B., Voigt, A. Monitoring α‐synuclein multimerization in vivo . FASEB J. 33, 2116–2131 (2019). www.fasebj.org